2006
DOI: 10.1590/s1519-69842006000400021
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and anatomy of a leaf mine in Vismia guianensis (Aubl.) Choisy (Clusiaceae) in a fragment of Brazilian Atlantic forest

Abstract: Mines or hyponomes are channels caused by larva miners consuming internal plant tissues. these miners live on the leaf and feed from these tissues. leaf mines are usually visible on the exterior of the leaf as serpentine paths, blotches, or other characteristic shapes of discolored tissues. Morphological and structural modifications undergone by mined leaves of Vismia guianensis (aubl.) Choisy are presented here with the purpose of elucidating their structure and to contribute to studies about insect-plant int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
(14 reference statements)
1
7
0
1
Order By: Relevance
“…In conclusion, the results reported in this paper indicate that the mines in both the species analyzed are linear, form real serpentines by consumption of parenchyma tissues of mesophyll, as stated in the literature (Mani 1964;Melo-de-Pinna et al 2002;Almeida-Cortez & Melo-de-Pinna 2006). Low larval mobility, associated with high miner visibility, makes the larva susceptible to parasitoids.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…In conclusion, the results reported in this paper indicate that the mines in both the species analyzed are linear, form real serpentines by consumption of parenchyma tissues of mesophyll, as stated in the literature (Mani 1964;Melo-de-Pinna et al 2002;Almeida-Cortez & Melo-de-Pinna 2006). Low larval mobility, associated with high miner visibility, makes the larva susceptible to parasitoids.…”
Section: Resultssupporting
confidence: 79%
“…11 and 13) and Commelina diffusa (Figs. 12 and 14) were observed that the mine is formed by consumption of parenchyma tissues of mesophyll, and, during tunnel formation, the miner consumes both palisade and spongy parenchyma; on the other hand, the epidermis and vascular tissue remain intact .This is independent of miner or plant groups, and the epidermis is considered by some authors as a physical protection for the larvae (Hering 1951;Melo-dePinna et al 2002;Almeida-Cortez & Melo-de-Pinna 2006). Weis & Berenbaum (1989) reported that miners do not form new tissues and this is the difference between the two types of endophytofagous (miner insects and insects that form galls).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…A preference for mesophyll tissues is a common feature in many other leaf-miners (e.g. Sehgal and Trehan 1963;Tauber and Tauber 1968;Sehgal 1971;De Clerck and Shorthouse 1985;Kato 1998;Almeida-Cortez and Melo De Pinna 2006). Several studies have related this behaviour to higher nitrogen or protein content and/or higher water content of the mesophyll (Kimmerer and Potter 1987;Trier and Mattson 1997).…”
Section: Feeding Strategy and Ecological Advantagesmentioning
confidence: 96%
“…Leafminers construct distinct leaf mines, most of which are quite conspicuous. For example, linear, serpentine, digitate, blotch and tentiform mines can be found on various types of plant leaves (Hering 1951, Kato 1984, Queiroz 2002, Sugiura and Yamazaki 2003, Almeida‐Cortez and Melo‐de‐Pinna 2006, Ayabe et al 2008, Yamazaki and Sugiura 2008; Fig. 1a–d).…”
Section: Leafminersmentioning
confidence: 99%